Multiple purpose tree use by farmers using indigenous knowledge in subhumid and semiarid northern Nigeria - Oyewole, B.; Carsky, R.J. (Informa UK Limited, 2001)
The northern Guinea savanna is generally known to be suitable for the production of annual crops of short-to-medium duration but is threatened with soil degradation because of inadequate organic inputs. Trees can be one important source of organic supplement to crop fields. Farmers' preferences for trees are related to a myriad of needs which vary in different environments. A survey was undertaken in Bauchi and Kaduna States of northern Nigeria to determine the extent of farmer knowledge in identifying niches for agroforestry trees. A total of 190 farmers were interviewed in Bauchi State and 154 farmers in Kaduna State.